α–E-catenin binds to dynamitin and regulates dynactin-mediated intracellular traffic - Lien, Wen-Hui (The Rockefeller University Press, 2008)
α–Epithelial catenin (E-catenin) is an important cell–cell adhesion protein. In this study, we show that α–E-catenin also regulates intracellular traffic by binding to the dynactin complex component dynamitin. Dynactin-mediated organelle trafficking is increased in α–E-catenin(−/−) keratinocytes, an effect that is reversed by expression of exogenous α–E-catenin. Disruption of adherens junctions in low-calcium media does not affect dynactin-mediated traffic, indicating that α–E-catenin regulates traffic independently from its function in cell–cell adhesion. Although neither the integrity of dynactin–dynein complexes nor their association with vesicles is affected by α–E-catenin, α–E-catenin is necessary for the attenuation of microtubule-dependent trafficking by the actin cytoskeleton. Because the actin-binding domain of α–E-catenin is necessary for this regulation, we hypothesize that α–E-catenin functions as a dynamic link between the dynactin complex and actin and, thus, integrates the microtubule and actin cytoskeleton during intracellular trafficking.